Contract-Boundary-Spanning Governance Mechanisms: Conceptualizing Fragmented and Globalized Production as Collectively Governed Entities - Jaakko Salminen (Indiana University Press, 2025)
Conceptualizing how private actors can and should control their supply chains is a tricky question with both economic and legal dimensions. The topic is of extreme importance in today’s global economy. On the one hand, this importance is highlighted by events such as the catastrophic and deadly collapse of the Rana Plaza factory building in Bangladesh and the economic fiasco of the Olkiluoto 3 nuclear power plant construction project in Finland, both arguably caused by the lack of effective supply chain governance. On the other hand, the potential benefits of successful supply chain governance, shown by examples such as open book accounting in automotive manufacturing, provide another perspective on the importance of focusing on supply chain governance. In this paper, I provide a framework for conceptualizing supply chain governance from a legal perspective. First, I combine the governance analytics of global value chain theory with research into compliance mechanisms and practical examples of contract boundary spanning governance mechanisms. This provides a preliminary typology that helps distinguish between adequate and inadequate governance mechanisms. Second, in contractually organized supply chains, governance mechanisms necessarily transgress contract boundaries and thus privity. This leads me to refer to them as contract-boundary-spanning governance mechanisms. To help conceptualize the requirements for attributing legal normative effects to such mechanisms, I propose using Teubner’s factual framework for evaluating liability in contract networks. Combined together, the typology and the framework provide a tool for evaluating and discussing the appropriateness of liability in different factual situations. This tool is not limited to any specific jurisdiction or doctrine and is thus trans-substantive. It enables further comparison of the legal doctrines available in different jurisdictions and transnationally for their potential in establishing liability in different configurations of supply chain governance.